POTENTIAL AND QUALITY OF FISHERY PRODUCTS IN EAST NUSA TENGGARA - Riris Roiska; Reni Lobo; Tri Wulandari; Febrina Rolin; Yusyam Leni; Dwinda Pangentasari; Ainun Rohmawati Bareta (Universitas Mataram, 2024)
Indonesia is a country that has quite large marine and fisheries resources and East Nusa Tenggara is one of the provinces in Indonesia that has very large fisheries resources, for this reason further exploration is being carried out to utilize these fisheries resources for both the domestic and export markets. This research is to find out about the marine and fisheries potential in East Nusa Tenggara and the quality of these fishery products by making direct observations at the Fish Quarantine Station for Quality Control and Safety of Fishery Products (SKIPM) Kupang, East Nusa Tenggara to find out about the fishery products that are trafficked. from the SKIPM. The results of the research show that East Nusa Tenggara has a very large and varied fisheries potential such as Anggoli, Skipjack, Cakalang, Crab Meat, Sweet Lip Fish, Grouper, Red Snapper, Onaga, Hermit crab, Mud Crab, Lobster, Beef Sei Tuna, Shark Fin, Mutira snails, Mackerel, Sea Cucumbers, Tuna Loin, Fan Shrimp, Ronggeng Shrimp, Seaweed and among these products Seaweed and Skipjack tuna are the highest number of fishery products trafficked from SKIPM Kupang, East Nusa Tenggara. The research results also show that 19 products originating from several fish processing units in East Nusa Tenggara province have met the maximum limit criteria for Escherichia coli contamination, namely <3 MPN/g with sensory pass quality or were still suitable and safe for consumption or marketing.